Writing at University - Adhiraj Chowdhury (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2019)
This article is a review of an online course on writing at the university level. It provides an overall summation of the chosen course based on the topics covered during the entire period of the course. As a conclusion, it provides a rounded opinion about the importance of such courses for non-native English speakers and writers.